OVERVIEW ON PERFORMANCE- BASED DESIGN OPTIMIZATION OF STEEL STRUCTURES SUBJECTED TO WIND LOAD BY USING E-TAB SOFTWARE - MEGHA JADHAV; NANDKUMAR PATIL (International Journal of Innovations in Engineering Research and Technology, 2021)
This paper presents a performance- based design optimization of tall steel framed structure exposed to wind loads of various levels by using E Tab software. Its earnings towards design a steel framed structure with an expectable and tolerable performance at four level wind during period of building. To forecast the inelastic drift behaviour of steel building a non-linear static pushover analysis is done.